2013
DOI: 10.3892/ijmm.2013.1384
|View full text |Cite
|
Sign up to set email alerts
|

miR-129-2 suppresses proliferation and migration of esophageal carcinoma cells through downregulation of SOX4 expression

Abstract: We report the emerging role of microRNA (miRNA) deregulation associated with activation of an oncogene SOX4 (a member of the SRY-related HMG-box) in esophageal carcinoma. Paired esophageal cancer and adjacent non-tumor tissues were obtained from 42 patients who underwent primary surgical resection for esophageal cancer. Experiments such as real-time PCR, western blot analysis, luciferase-reporter assay, cell proliferation and colony formation assays, in vitro migration and invasion assays, and a wound-healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 40 publications
(43 reference statements)
5
52
0
Order By: Relevance
“…Previous studies have revealed that protein levels of Sox4 were controlled by several miRNAs, such as miR-129-2, miR-138, miR-203 and miR-204 [23,24,25,26]. Although the reason why multiple microRNAs regulate a single mRNA remains poorly understood until now, our study together with these reports add a novel mechanism for the up-regulation of Sox4 in human cancers.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have revealed that protein levels of Sox4 were controlled by several miRNAs, such as miR-129-2, miR-138, miR-203 and miR-204 [23,24,25,26]. Although the reason why multiple microRNAs regulate a single mRNA remains poorly understood until now, our study together with these reports add a novel mechanism for the up-regulation of Sox4 in human cancers.…”
Section: Discussionmentioning
confidence: 63%
“…microRNAs have emerged as key regulators of the immune system, including regulation of cell cycle (miR-34c, miR-138, miR-193b, miR-129, and let-7f), induction of innate immunity (let-7f, miR-146b, miR-155, miR-192, miR-223, miR-451), and the development and differentiation of B and T cells (miR-34c, miR-181a, miR17-92 cluster) (4,10,17,20,26,45,50,52,53).…”
mentioning
confidence: 99%
“…However, their 3'-prime products are different, which are named miR-129-1-3p and miR-129-2-3p, respectively (6,7). Dysregulation of miR-129-2 is frequently detected in solid tumors (8)(9)(10)(11)(12)(13). However, the role of miR-129-2 in breast cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%